Promising practices in recruitment, remediation, and retention / Gerald H Gaither [editor]
"Recruitment, remediation, and retention have become high-visibility issues for higher education as these matters receive increased scrutiny from government, the media, and consumers concerned about receiving greater results. This volume ... captures some of the best practices found in progressive institutions and programs in the United States on these three issues. Further, it offers a demographic profile surrounding the issues and a set of practical resources, primarily focusing on successful programs--including Web sites and other electronic resources--to assist practitioners in achieving the goals of their own programs."--Publisher